Direct gap photoluminescence of n -type tensile-strained Ge-on-Si - Sun, Xiaochen; Liu, Jifeng; Kimerling, Lionel C.; Michel, Jurgen (Applied physics letters, 2009)
Room temperature direct gap photoluminescence (PL) was observed from n -type tensile-strained epitaxial Ge-on-Si. The PL intensity increases with n -type doping due to a higher electron population in the direct Γ valley as a result of increased Fermi level. The direct gap emission also increases with temperature due to thermal excitation of electrons into the direct Γ valley, exhibiting robustness to heating effects. These unique properties of direct gap emission in an indirect gap material agree with our theoretical model and make Ge a promising light emitting material in 1550 nm communication band.